EVALUATION OF THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM AND ITS IMPLICATIONS FOR TEACHER READINESS IN SECONDARY SCHOOLS - Yance Manoppo (Adisam Publisher, 2026)
This research aims to evaluate the implementation of the Independent Learning Curriculum and its implications for teacher readiness in secondary schools through a literature review. The Merdeka Belajar Curriculum is an educational initiative that provides teachers with more flexibility to create relevant and contextual learning according to students' needs. This study analyzes various literature that discusses the implementation of this curriculum, as well as the challenges and opportunities faced by teachers. The results of the study show that although there is great potential in this curriculum to improve the quality of education, many teachers still face difficulties in adopting the new approaches required. Factors such as lack of adequate training, limited infrastructure support, and resistance to change are the main obstacles. Therefore, this research suggests the need for a more comprehensive professional development strategy, managerial support, and closer collaboration between schools, parents, and communities to ensure the successful implementation of the Merdeka Belajar Curriculum. Thus, it is hoped that this research can provide deeper insight and become the basis for developing more effective education policies.